Desempenho auditivo ao longo do tempo e satisfação dos usuários de implante coclear com perda auditiva pós-lingual - Buarque, Laísa Flávia Soares Fernandes Peixoto (2013)
Most cochlear implant (CI) users, who suffer from post lingual hearing loss, are able to perceive sounds and comprehend speech after the implant. The prediction of maximal benefit over time, with the use of CI, can be useful for counseling patients about their expectations in using the new device. The measurement of satisfaction should be of primary interest in medical intervention, as the results may be used for intervention feedback. The purpose of this study is to analyze auditory performance of CI over time, as well as to evaluate users‟ satisfaction. Therefore two types of study designs were employed: a) retrospective cohort study with the analysis of medical records from 59 subjects about auditory performance before and after surgery. Results were submitted to the Kaplan -Meier estimator of cumulative probability and compared to prognostic factors of auditory performance using the logrank test. b) A sectional study design was conducted to evaluate the satisfaction of 51 subjects. The instrument consists of two specific questionnaires: Satisfaction with Amplification in Daily Life SADL and International Outcome Inventory Cochlear Implant IOI- CI. Results show statistical significant differences (p<0,001) in auditory performance before and after CI. The majority obtained satisfactory results of CI use during the first six months. Logrank tests does not indicate significant correlation between the analyzed covariates and the time in which adequate speech perception occurs. SADL e IOI-CI questionnaires indicate that most of the CI users are satisfied with their devices. The SADL detected a 27, 5% insatisfaction amongst CI users in relation to services and costs involved with the CI. The results of the IOI show 4% of insatisfaction with the use of CI and the social environment. In conclusion CI is capable to rehabilitate social auditory function in a short period of time and CI users demonstrate satisfaction with auditory, social and psychological gain offered through CI device